Generation of surface waves due to initial axisymmetric surface disturbance in water with a porous bottom - Kundu, Prabir Kumar; Mandal, B.N. (Zielona Góra: Uniwersytet Zielonogórski)
A two-dimensional Cauchy Poisson problem for water with a porous bottom generated by an axisymmetric initial surface disturbance is investigated here. The problem is formulated as an initial value problem for the velocity potential describing the motion in the fluid. The Laplace and Hankel transform techniques have been used in the mathematical analysis to obtain the form of the free surface in terms of a multiple infinite integral.
Keywords: axisymmetric surface disturbance; porous bottom; Laplace and Hankel transform; method of stationary phase; free surface depression